Sex‐specific activation of SK current by isoproterenol facilitates action potential triangulation and arrhythmogenesis in rabbit ventricles. (19th July 2018) - Chen, Mu; Yin, Dechun; Guo, Shuai; Xu, Dong‐Zhu; Wang, Zhuo; Chen, Zhenhui; Rubart‐von der Lohe, Michael; Lin, Shien‐Fong; Everett, IV, Thomas H.; Weiss, James N.; Chen, Peng‐Sheng
Abstract : Key Points: It is unknown if a sex difference exists in cardiac apamin‐sensitive small conductance Ca 2+ ‐activated K + (SK) current ( I KAS ). There is no sex difference in I KAS in the basal condition. However, there is larger I KAS in female rabbit ventricles than in male during isoproterenol infusion. I KAS activation by isoproterenol leads to action potential triangulation in females, indicating its abundant activation at early phases of repolarization. I KAS activation in females induces negative Ca 2+ –voltage coupling and promotes electromechanically discordant phase 2 repolarization alternans. I KAS is important in the mechanisms of ventricular fibrillation in females during sympathetic stimulation. Abstract: Sex has a large influence on cardiac electrophysiological properties. Whether sex differences exist in apamin‐sensitive small conductance Ca 2+ ‐activated K + (SK) current ( I KAS ) remains unknown. We performed optical mapping, transmembrane potential, patch clamp, western blot and immunostaining in 62 normal rabbit ventricles, including 32 females and 30 males. I KAS blockade by apamin only minimally prolonged action potential (AP) duration (APD) in the basal condition for both sexes, but significantly prolonged APD in the presence of isoproterenol in females. Apamin prolonged APD at the level of 25% repolarization (APD25 ) more prominently than APD at the level of 80% repolarization (APD80 ), consequently reversing isoproterenol‐induced AP triangulation in females. In comparison, apamin prolonged APD to a significantly lesser extent in males and failed to restore the AP plateau during isoproterenol infusion. I KAS in males did not respond to the L‐type calcium current agonist BayK8644, but was amplified by the casein kinase 2 (CK2) inhibitor 4, 5, 6, 7‐tetrabromobenzotriazole. In addition, whole‐cell outward I KAS densities in ventricular cardiomyocytes were significantly larger in females than in males. SK channel subtype 2 (SK2) protein expression was higher and the CK2/SK2 ratio was lower in females than in males. I KAS activation in females induced negative intracellular Ca 2+ –voltage coupling, promoted electromechanically discordant phase 2 repolarization alternans and facilitated ventricular fibrillation (VF). Apamin eliminated the negative Ca 2+ –voltage coupling, attenuated alternans and reduced VF inducibility, phase singularities and dominant frequencies in females, but not in males. We conclude that β‐adrenergic stimulation activates ventricular I KAS in females to a much greater extent than in males. I KAS activation plays an important role in ventricular arrhythmogenesis in females during sympathetic stimulation. Key Points: It is unknown if a sex difference exists in cardiac apamin‐sensitive small conductance Ca 2+ ‐activated K + (SK) current ( I KAS ). There is no sex difference in I KAS in the basal condition. However, there is larger I KAS in female rabbit ventricles than in male during isoproterenol infusion. I KAS activation by isoproterenol leads to action potential triangulation in females, indicating its abundant activation at early phases of repolarization. I KAS activation in females induces negative Ca 2+ –voltage coupling and promotes electromechanically discordant phase 2 repolarization alternans. I KAS is important in the mechanisms of ventricular fibrillation in females during sympathetic stimulation.